Is There Americanization in Catalan Election Campaigns? A Decade of Electoral Communication Strategies From Postmodernist Perspective. (March 2018) - Pont-Sorribes, Carles; Cortiñas-Rovira, Sergi; Mauri, Marcel; Alonso-Marcos, Felipe
We examine how Catalan election campaigns have evolved to postmodernization, a concept coined by Pippa Norris to refer to the current political scenario and how this is reflected in different electoral phases. We analyzed four electoral campaigns covering a decade (2003-2012) through 27 face-to-face in-depth interviews conducted with campaign managers for nine political parties. The results indicate that, although Catalan politics is progressing toward the postmodern phase, there are still aspects that are far from fully adapted to the changes affecting all levels of society. Catalan political parties seem to be more comfortable with modern or classical political approaches—such as control over traditional media—and are but slowly reacting to other issues such as citizen demands for more access to, and prominence in, politics.